The DESIGN AND CONSTRUCTION OF BANK CAPACITY REGULATOR USING FAST CHARGE METHOD FOR MILITARY BOOT SHOES - Prastyanto, Nanang; Widiatmoko, Dekki; Sridaryono, Aguk (Pustaka Poltekad, 2021)
Abstract: Indonesia is an archipelagic country with 17,504 islands, geographically Indonesia is located between the continents of Asia and Australia and the two Pacific and Indian Oceans. In support of maintaining the sovereignty of the Republic of Indonesia, especially the land dimension, equipment is needed to support the main tasks. The majority of the equipment used requires electrical energy in its use. Meanwhile, in carrying out their duties, while maintaining sovereignty in border areas, the geography is in the form of tropical forests with minimal fields of electrical energy as an energy supply. Therefore, researchers develop a source of electrical energy by utilizing footsteps, which is a solution for recharging electrical energy. In developing the tool, the method used is fast charging. The mini generator located on the shoe is expected to be a solution for recharging as a supply of electrical energy for equipment to support basic tasks. Capacitor Bank is used to stabilize the input voltage of the mini generator so that recharging becomes more stable and charging faster.